A Smart Leader in VUCA World: Presenting Key Components of Strategic Leadership Using SLR Method - Kumar, Amit; Anand, Gunjan; Nandedkar, Tarika (Lembaga Penerbit Fakultas Ekonomi dan Bisns, Universitas Trisakti, 2024)
The current study compiles and summarizes the key findings of the researches conducted on strategic leadership to meet VUCA world’s demand for organizational excellence, sustainable growth, competitive advantages and people centric approach using SPAR-4-SLR protocol technique. Reputed international journals of ABDC A*, A & B ranking are referred to extract corresponding findings of quality research articles on strategic intents of progressive and transformational leadership. Using SLR method the study tries to collate relevant evidences based upon ‘systematic procedures and rationales’ disclosing key parameters of smart leadership required in today’s dynamic business world. Here, ‘smart’ word refers to a ‘learnt leader through experience’ than ‘a trained leader in a business school’. With the help of ‘Systematic Literature Review (SLR)’ technique, the study finds ‘idealized influence (4 component), intellectual stimulation (2 factors), individual consideration (4 factors) and inspirational motivation (4 factors) are identified as the key components of a strategic leadership in today’s VUCA world. The research also presents four elements of a smart leader viz. social intelligence, emotional intelligence, professional wisdom and spiritual intelligence.